Spawning population characteristics of horseshoe crab Tachypleus gigas (Muller, 1785) at Pantai Balok - Tan, Ai Nee (2011)
The population monitoring data for horseshoe crab in its spawning and nursery sites is scarce. Hence, the population status of the horseshoe crab is poorly understood as the basic data for population assessment has not been collected. The public awareness on the ecological importance of the horseshoe crabs is low. Three horseshoe crab species reported in coastal waters of Malaysia, namely Carcinoscorpius rotundicauda, Tachypleus gigas, and Tachypleus tridentatus. This study aimed to determine size-frequency distribution, length-weight relationship and sex ratio of the population of horseshoe crab T. gigas. An attempt was also made to study the infestation of epibiont on the carapace and to report the condition of carapaces. A total of 86 males and 75 females T. gigas sampled from Pantai Balok were examined. Most horseshoe crabs came ashore in amplexus pairs. As compared to Atlantic species, there was no sighting of satellite male competing with the male in amplexus pairs during spawning season. The uncommon occurrence of tandem amplexus was also observed at this study site. Female T. gigas is bigger in size than the male. Size-frequency data indicated 69.8% of male horseshoe crabs belonged to size group of 151-200 mm while 53.3% of females were classified into size group of 201-250 mm. The largest female recorded was with mean prosomal length and width of 154.4 mm and 246.9 mm, respectively. Females were heavier than the males with mean body weight of 824.4 g. Tail ratio (TR) ranged from 0.21 to 0.57 for males and 0.39 to 0.56 for females T.gigas. As for flatness of carapace (FC), males were ranged from 0.60 to 1.14 and females from 0.76 to 1.19. Student’s T-test showed significant sex differences for TR and FC (P < 0.05). Female T. gigas has a flatter carapace and shorter telson than the male. The length-weight relationships were linear between logarithmic weight and logarithmic length for both sexes. The values of the slopes for both males and females were more than 1 thus exhibited a positive allometry where increment of the weight is more rapid as compared to prosomal length. Analysis of covariance revealed significant difference between the slopes of both sexes (F = 3085.391 with df 1,153; P < 0.05). Weights of males and females T. gigas increased with exponentials of 2.557 and 2.837, respectively. Values for the coefficient of determination (r2) for regression of length with weight were, 0.611 for males and 0.726 for females. All individual horseshoe crabs were adults categorized under fourteenth, fifteenth and sixteenth instar stage. Approximately 64.7% of male individuals belonged under the fourteenth instar stage and 55.3% of female individuals in fifteenth instar stage. Juvenile or young adult was not found at this study site. Males at fourteenth instar stage were more prone to epibiont infestation. Four epibiont species were found on carapaces of T. gigas, namely acorn barnacle Balanus, pedunculate barnacle Octolasmis, conical slipper shells Calyptraea, and flat slipper shells Crepidula. The epibionts were distributed on the dorsal and ventral sides of the carapace. Monsoon season and horseshoe crab harvesting influence the sex ratio at the study site. Heavy precipitation, strong surf and flooding occur during monsoon season and hence fewer horseshoe crabs were sighted. As compared to female, higher proportion of males was sampled because female horseshoe crab was harvested to make delicacy dishes and exported to neighboring country,Thailand. The carapace, lateral eyes and telson of each individual horseshoe crab were carefully examined. Most males had eyes covered by epibiont with traumatic injured carapaces while most females had broken telsons. However, T. gigas having covered eyes, injured carapace and broken telson was not exempted for being an amplexus pair to spawn onshore. Two T. gigas having telson abnormalities (stubby, curved) could be at risk of being stranded. The traumatic injuries of carapaces could be due to collision with boats as this study site is a landing port for fishing boats. This study will serve as a basis for the implementation of effective conservation strategies and management planning for the horseshoe crab species to ensure their continuous survival. It is hoped that the findings of this study will provide both qualitative and quantitative baseline information for future work.